THE RELATIONSHIP BETWEEN ACADEMIC ACHIEVEMENT AND POLITICAL VIEWS IN INDONESIA - SEVENTILOFA, I GUSTI NGURAH OCTOVA (GANEC SWARA, 2024)
This research examines the relationship between academic achievement and political views in Indonesia, addressing a significant gap in the existing literature within the Indonesian context. With the country's diverse socio-political landscape and rapid educational developments, understanding how academic attainment influences political perspectives is crucial for informing policy and fostering democratic engagement. Utilizing a quantitative research design, data was collected through a cross-sectional survey distributed among a diverse sample of participants representing various socio-economic backgrounds, educational levels, and geographic regions across Indonesia. The survey instrument included measures to assess academic achievement, political views, socio-economic factors, and other relevant variables.Preliminary analysis indicates a significant correlation between academic achievement and political views, with individuals of higher educational attainment tending to hold more liberal and progressive political perspectives. However, the relationship is nuanced and influenced by contextual factors such as socio-economic background, geographic location, and access to information.This study contributes to the existing literature by providing empirical evidence on the relationship between academic achievement and political views specifically within the Indonesian context. The findings have implications for educational policy, democratic participation, and social cohesion, highlighting the importance of addressing disparities in educational access and quality to promote informed and inclusive political discourse.